PENGARUH PENERAPAN METODE GUIDED WRITING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS CERITA PENDEK PADA SISWA KELAS V SDN CIGINTUNG 4 - Ayuni Nuraeni; Siti Nurwahidah, Lina; Lestari, Rahayu; Pratiwi, Mutia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low writing skills of fifth-grade elementary school students in composing short stories in Indonesian learning. The research aims to determine the effect of the Guided Writing method assisted by image media on students’ short story writing skills. This study employed a quantitative approach with an experimental method using a pretest-posttest control group design. The population consisted of third-grade elementary school students, with samples divided into an experimental class and a control class. Data were collected through writing test and observation sheets, then analyzed using statistical techniques to measure the significance of differences between groups. The result showed that the implementation of the Guided Writing method with image media had a positive and significant effect on students’ writing skills. Students in the experimental class demonstrated better improvement in organizing ideas, developing story elements, and using appropriate language compared to those in the control class. The findings indicate that structured guidance through pre-writing, writing, and post-writing stages, supported by visual stimuli, effectively enhances students’ ability to express ideas in written from. Therefore, the Guided Writing method assisted by image media can be recommended as an effective instructional strategy to improve short story writing skills in elementary school students.